Living Standards and Economic Vulnerability in Turkey between 1987 and 1994 - Ruslan Yemtsov (Institute for the Study of Labor (IZA), 2001)
Until recently, poverty was a relatively unexplored field of studies in Turkey. This is one of the first attempts outside Turkey to use household survey data from two nationally representative surveys conducted in 1987 and 1994 to get a picture of poverty and its main driving forces. The 1994 data remain until today the latest household level data available for Turkey. The paper finds that Turkey does not face a problem of absolute poverty by the standards of a developing country (in 1994 only 2.5 percent of population lived at less than 1 dollar a day at 1985 purchasing power parity). However, applying a standard that is adequate to Turkey?s level of development we find that 7 percent of the population were not able to afford a minimum food basket in 1994 and 36 percent were below the threshold that included alongside minimum food requirements also essential non-food spending. There was a rather small reduction in the poverty risk in Turkey between 1987 and 1994, despite an impressive economic growth, - largely due to negative effects of the macroeconomic crisis of 1996. Poverty in Turkey affects mostly specific groups of the population. Employment and earnings opportunities are key determinants of poverty risks. The profile of poverty by labor market characteristics has remained stable in the 1987-94 period. Macroeconomic and demographic factors (falling fertility and migration from the poorest rural areas to cities) were the main driving forces behind changes in the number of poor.
Keywords: I3; J4; 330; Inequality; poverty; Gini coefficient; poverty line; minimum consumption basket; cumulative distribution function; consumer price index; Armut; Einkommensverteilung; Lebensstandard; Arbeitslosigkeit; Türkei